(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Kontrola orzeczeń sądów arbitrażowych przez sądy krajowe (państwowe) należy do obszaru zagadnień relacji sądu państwowego i sądu polubownego. W zasadzie każdy system prawny, który sankcjonuje wyroki sądów prywatnych, poprzez zrównanie ich mocy z wyrokami sądów państwowych, jednocześnie przewiduje określone formy kontroli orzeczeń zapadłych przed sądem polubownym, czyli zawiera regulacje dotyczące postępowania przed państwowym sądem krajowym, będącym możliwym następstwem arbitrażu, którego przedmiotem jest kontrola orzeczenia zapadłego przed sądem polubownym. As a general rule, every legal system in the world has regulations governing proceedings before a national court of law; some of the proceedings are possibly instituted subsequently to arbitration and thus review awards issued in arbitration proceedings. Such review may be carried out, first, where there is a motion to have the arbitral award set aside (deemed invalid, nullified) or where the arbitral award is to be recognized or enforced judicially. The general objective of the review is to secure legal transactions by eliminating decisions made in the conduct of arbitration proceedings, if their outcome may not be authorized by a state, mainly due to their disaccord with the basic principles of legal order. The scope of the review may vary as it is dependent upon internal regulations of a given state, especially whether the aforesaid regulations were set forth in compliance with the UNCITRAL Model Law, or whether the legal system provides for separate provisions on arbitral awards issued at a territory of a given country but within international arbitration proceedings, or finally whether the parties, at their discretion, may be precluded from applying to have an arbitral award set aside.